Efektivitas Penambahan Elisitor Asam Jasmonik dalam Peningkatan Sintesis Senyawa Bioaktif Andrografolid pada Kultur Suspensi Sel Sambiloto (Effectiveness of Jasmonic Acid Elicitor Addition for Andrographolide Synthesis Induction of Sambiloto Culture) - Noor Aini Habibah (Biosaintifika: Journal of Biology & Biology Education, 2009)
In this research, we have studied synthesis of improvement of andrographolid bioactive compound on cell culture of sambiloto by addition of jasmonic acid. The essential problems in this research are firstly, the effects of addition of jasmonic acid either can induce or not andrographolide synthesis improvement of cell culture of sambiloto and secondly, to observe the largest content of andrographolide in jasmonic acid concentrations. Meanwhile, the purpose of this research are to observe the functions of jasmonic acid elicitor for induction of andrographolide synthesis improvement of cell culture of sambiloto and to optimize jasmonic acid concentrations which can produce the largest andrographolide content. The independent variable is concentration of addition of jasmonic acid on cell culture and the dependent variable are the growth of cell suspension culture and andrographolide bioactive content. Experiment result show that the optimum medium of sambiloto cell consist of Murashige Skoog (1962) medium supplemented by 0,5 ppm kinetin and 2,4-D 5 ppm. The cell growth phases are the followings : lag phase at age of 0-5 days, exponential phase of 5-15 days, and stationary phase at age of longer than 15 days. The highest andrographolide was 4,66 x 10-2 reached in cell culture was supplemented with 10 ÂµM jasmonic acid. Keywords : andrographolide, sambiloto cell suspension culture, jasmonic acid elicitor.